Liver fluke infestation in Kansas fed slaughter cattle - S.B. Laudert (Kansas Agricultural Experiment Station Research Reports, 1989)
Feedlot cattle from 1,687 pens totaling 290,183 head were evaluated at slaughter for the presence of liver flukes. Overall, 4.92% of the cattle were found to be infected. Only 15.2% of all pens of cattle were found to be completely free of flukes. However, only 5.3% of the pens had greater than 15% of the cattle infested. Beef steers had a higher level of infestation (5.2%) than beef heifers (4.4%). Holstein steers had an overall infestation rate of 4.4%.
Keywords: Cattlemen& #x27; s Day; 1989; Kansas Agricultural Experiment Station contribution; no. 89-567-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 567; Beef; Liver fluke; Slaughter cattle